Gastric headache: Historical concept still widely prevalent - Anil Kakunje; Kiran Kumar; Vijay Ramachandran (Wolters Kluwer Medknow Publications, 2015)
Ethno-medicine refers to the study of traditional medical practice which is concerned with the cultural interpretation of health, diseases and illness and also addresses the healthcare-seeking process and healing practices. Headache is one of the common symptom for consultation with a doctor. Several patients visiting doctors and specialists with the complaint of headache, attribute the cause to gastritis, gas or to any similar terminology in their local language. Since, the cause connects between head and stomach the condition is known as "gastric headache". The knowledge of gastric headache and its description details were greatly contributed by the medical traditions of ancient Greece, Persia Egypt, India, and China. The possible causality of the gastrointestinal diseases in inducing headaches has been little investigated. We do see a significant proportion of patients visiting varied specialists attributing headache to gas/gastritis. We believe that attribution patterns, explanatory models and research is needed to study gastritis/gas as a cause for headache in different cultures. The difference in the understanding and beliefs of the illness between the clinician and patient can result in inappropriate assessment or dis-satisfaction.